Poznańskie lata Henryka Ułaszyna - Skarżyński, Mirosław (Wydawnictwo „Poznańskie Studia Polonistyczne" i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
Henryk Ułaszyn (1874–1956), linguist, specialist in Slavic and Polish languages and literatures, disciple of Baudouin de Courtenay and a professor of Poznań University, was not only a scholar but also a prominent social activist and freethinker of the interwar period. His liberal and anticlerical views, overtly expressed in public talks and lectures, the articles published in the press and in pamphlets, as well as his uncompromising and hard hitting polemics in his public addresses in defence of science and reason, led ultimately to a number of conflicts with the local academic community. Ułaszyn was attacked by Catholic and right-wing press, he was even physically assaulted. The article, researched and based on archival material, focuses on this particular aspect in his biography.
Keywords: history of Polish linguistics; Henryk Ułaszyn; Poznań University; Polish freethinkers